1997
DOI: 10.1001/archpsyc.1997.01830130062013
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Risk Factors Predicting Grief Intensity Following Pregnancy Loss

Abstract: A relatively long preloss pregnancy, a more neurotic personality, more preloss psychiatric symptoms, and the absence of living children appear to be important risk factors for stronger grief responses in women following a pregnancy loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
0
20

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 34 publications
3
97
0
20
Order By: Relevance
“…Somewhat consistent results are found when level of grief after miscarriage and the presence of prior psychiatric symptoms are studied, with preloss coping capacity seeming to be predictive of level of grief. Finally, the absence of studies on the effects of social support and religious participation on level of grief following miscarriage prevents any conclusions from being drawn [37][38][39][40][41][42][43][44][45] .…”
Section: Results Of the Reviewmentioning
confidence: 99%
“…Somewhat consistent results are found when level of grief after miscarriage and the presence of prior psychiatric symptoms are studied, with preloss coping capacity seeming to be predictive of level of grief. Finally, the absence of studies on the effects of social support and religious participation on level of grief following miscarriage prevents any conclusions from being drawn [37][38][39][40][41][42][43][44][45] .…”
Section: Results Of the Reviewmentioning
confidence: 99%
“…Because female individuals who compose a mother's social support network likely view miscarriage as less severe than stillbirth, it is likely that they provide less support to women who experience miscarriage. Poor social support is related to higher grief reactions and more severe psychiatric symptoms following perinatal loss (Forrest et al, 1982;Hughes & Riches, 2003;Janssen et al, 1997). If the level of support individuals provide is dependent upon perceptions of perinatal loss, it is important that accurate knowledge of the grief process following varying types of perinatal loss is dispersed to improve the support provided to these women and possibly prevent prolonged and intensified emotional disturbances.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…More intense and prolonged grief reactions have been detected in women who received less support from their social network (Hughes & Riches, 2003;Janssen et al, 1997). In fact, Forrest, Standish and Baum (1982) showed that social isolation and poor relations are correlated with high grief responses following perinatal loss.…”
mentioning
confidence: 99%
“…Longitudinal studies have demonstrated that in a normal grieving process, grief declines over a period of 2 years after the pregnancy loss. 4,5 The specific aims and objectives of the study were…”
Section: Introductionmentioning
confidence: 99%